A new Centaurea species (sect. Centaurea) from south-western Türkiye - Uysal, Tuna; Bozkurt, Meryem; Şirin, Emrah; Ertuğrul, Kuddisi (Phytotaxa, 2026)
Centaurea stadiae Uysal (sect. Centaurea) is described as new to science from Türkiye. Morphology, especially seed surface, karyology and molecular data were used to distinguish the new species from its presumed relatives. The new taxon appears morphologically similar to C. pelia which is endemic to Greece but is clearly separated mainly by having corymbose inflorescence and numerous flowers as well as more narrow involucres and reddish narrow and triangular appendage borders. Moreover, C. stadiae is a tetraploid species unlike C. pelia with a diploid chromosome number. Although the new species appears similar to C. dichroa, it can be easily distinguished by its dirty white flowers, triangular appendages, and smaller achenes. Additionally, a modified identification key is provided, and the species ecology and phenology are given.